Arctic copepod copper sensitivity and comparison with Antarctic and temperate copepods - Heuschele, Jan; Dinh, Khuong V.; Lode, Torben; Jager, Tjalling; Borgå, Katrine (Ecotoxicology, 2024)
The ongoing global climate crisis increases temperatures in polar regions faster and with greater magnitude than elsewhere. The decline of Arctic sea ice opens up new passages, eventually leading to higher anthropogenic activities such as shipping, fishing, and mining. Climate change and anthropogenic activities will increase contaminant transport from temperate to Arctic regions. The shipping industry uses copper as an antifouling coating. Copper is an essential element but becomes toxic at excess concentrations, and its use may inadvertently affect non-target organisms such as copepods. Copper affects copepods by lowering reproductive output, prolonging developmental time, and causing increased mortality. As data on copper sensitivity of polar copepods at low temperatures are rare, we conducted onboard survival experiments with the Arctic region’s most common copepod species (Calanus finmarchicus, C. glacialis, C. hyperboreus). Acute survival tests were done for up to 8 days on individuals in 70 ml bottles at 1 °C with nominal copper concentrations ranging from 3 to 480 μg L−1. We used a reduced General Unified Threshold model for Survival (GUTS) to analyse the data, and placed our results in the context of the few published copper sensitivity data of the Antarctic and temperate copepod species at low temperatures. The sensitivity of Cu exposure was similar between the three Calanus species. However, a model comparison suggests that the tested C. glacialis population is less sensitive than the other two species in our experiments. Compared to published data, the three Arctic species appear slightly less sensitive to copper compared to their Antarctic counterparts but more compared to their temperate ones. Our literature search revealed only a few available studies on the copper sensitivity of polar copepods. In the future, this species group will be exposed to more pollutants, which warrants more studies to predict potential risks, especially given possible interactions with environmental factors.
Keywords: Antarktis; copepoder; forurensning; hoppekreps; klimaendringer; marin biologi; miljøgifter; polarområdene; økotoksikologi

Three artotrogids (Crustacea: Copepoda: Siphonostomatoida) from the Ross Sea, Antarctica - Conradi, Mercedes (Polar Research, 2014)
The Artotrogidae, one of the most primitive of siphonostomatoid families, consists currently of 117 species in 21 genera. Most of these species (65%) are poorly or incompletely described since they have been rarely recorded in recent decades and, when encountered, have been found in very low numbers. During the 19th Italian Antarctic Expedition, with the RV Italica, to the Ross Sea in austral summer 2004, some artotrogid copepods were collected. This paper redescribes two species of artotrogid copepods, which are known only from the Southern Ocean, Neobradypontius neglectus and Cryptopontiuslatus, and describes for the first time a male of the genus Neobradypontius. Furthermore, a new species is described and added to Sestropontius, increasing the number of known species of this genus to three. The main discrepancies between the original descriptions and the specimens of the two species collected from the Ross Sea redescribed here were on the armature of the antennary exopod and leg 5. The new species, Sestropontius italicae, shares with its most similar congener, S. mckinnoni, the armature of the third endopodal segment of leg 1 and leg 2 and that of the third exopodal segment of leg 4. However, the segmentation of the antennae and the armature on the antennary exopod are different. Keywords: Antarctica; Artotrogidae; redescription; Neobradypontius; Sestropontius; Cryptopontius.
Keywords: Rosshavet; Sørishavet; copepoder; ekspedisjoner; hoppekreps; marin biologi; zoologi

Antarctic krill Thysanoessa macrura fills a major gap in marine lipogenic pathways - Kattner, Gerhard; Hagen, Wilhelm; Falk-Petersen, Stig; Sargent, John R.; Henderson R. James (Marine Ecology Progress Series, 1996)
The unique predominance of oleyl alcohols (18:1) is the striking characteristic of the lipids of the Antarctic euphausiid Thysanoessa macrura. The 2 isomers 18:1(n-9) and 18:1(n-7) occurred in similar proportions in the wax esters of T. macrura and comprised up to 80% of the total fatty alcohols. The remainder consisted mostly of the 20:1(n-9) alcohol along with small amounts of the 22:1(n-11) alcohol. No marine zooplankton species has previously been reported which produces wax esters with significant amounts of 18 carbon fatty alcohols. T. macrura specimens were collected in the high Antarctic Weddell Sea during autumn 1992 and summer 1993. Their lipid levels were high, about 40 to 50% of the dry mass with up to 70% of the total lipid as wax esters. The wax ester fatty acids were dominated by the saturates 14:0 and 16:0, which, along with the monounsaturate 18:1(n-9), accounted for more than 80% of the total fatty acids. Phospholipids contained high levels of (n-3) polyunsaturated fatty acids (20:5 and 22:6) typical of membrane lipids from marine zooplankton. The precise significance of the unique wax ester composition in T. macrura is not clear but this discovery underscores the biochemical adaptability of Antarctic zooplankton species to a constantly cold and highly seasonal polar environment.
Keywords: Sørishavet; Weddellhavet; biokjemi; dyreplankton; hoppekreps; krill; marin biologi; zooplankton; økologi

Predatory feeding behavior of an Antarctic marine copepod, Euchaeta antarctica - Yen, Jeannette (Polar Research, 1991)
Keywords: Antarktis; fytoplankton; hoppekreps; marin biologi